Analisis Pengaruh Rumble Strips dalam Mereduksi Kecepatan Kendaraan - Ari Setiawan; Emelda Raudhati (Universitas Batanghari Jambi, 2023)
The number of traffic accidents has increased every year, especially in Jambi City. One of the government's efforts to reduce the number of traffic accidents is to make regulations limiting speed in pedestrian areas, especially school areas. One of the speed limiters that is widely used is the rumble strip, especially in the SDN 206 area of Jambi City. This study analyzes the effect of Rumble Strips in reducing the speed of motorbikes and light vehicles. The results obtained for the speed of the motorbike before Rumble Strips was 38.24 km/hour while after Rumble Strips it was 23.81 km/hour and the resulting reduction value was 14.43 km/hour. The speed of light vehicles before Rumble Strips was 32.07 km/hour while after Rumble Strips was 22.75 km/hour and the resulting reduction value was 9.32 km/hour. The speed of light vehicles before Rumble Strips was 32.40 km/hour while after Rumble Strips was 17.07 km/hour and the resulting reduction value was 15.33 km/hour. So that from the results of the analysis it was found that motorcycles, light vehicles and heavy vehicles were able to reduce well.